The Essence of in Absentia in The Examination of Corruption Cases - I Made Suarnawan (Universitas Airlangga, 2020)
The legal vacuum associated with in absentia examinations can benefit corruptors. Unprofessional law enforcement officers can help the suspect by providing opportunities or facilities for the suspect to escape in order to suspend the investigation. In the event where the investigation is suspended for this reason, then there would be no legal certainty and fairness in the effort to recover the financial loss of the State. Article 38 of the PTPK Law only applies in the examination of cases without the presence of the defendant in the trial. In Absentia is a suspect or defendant whose whereabouts is not known, does not present for the examination of the case or whom cannot be forced to be present in the trial. The general philosophy of in absentia examination in corruption cases is that criminal acts of corruption are not justified, as they result in detrimental loss of the country's finances or economy. In the essence, in absentia examination is an effort to eradicate corruption in a serious or extraordinary manner because corruption is a serious crime and as an effort to recover the country's financial and economy loss.